Cadangan Emas, Harga Emas dan Stabilitas Mata Uang di Negara Islam - Arina Azwani (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2021)
This study ained to determine ‘the impact of gold reserves accumulation and gold price against exchange rate stability in USD. Observation on four Islamic countries in the world, Malaysia, Qatar, Indonesia and Pakistan that incorporated in OIC (Organization of Islamic Coorporation) with observation period within 18 years from 2000 – 2017 by using panel data regression method. Based on result of partial test, gold reserves does not have positive significant effect against exchange rate while gold price have positive significance effect against exchange rate to four selected Islamic countries. The result on this study want to be more encouraging the government especially in four Islamic countries to increase the stock of gold reserves because of the commodity and the value of gold that proven stable and to apply monetary policy based on Dinar Dirham rather than paper currency, the development of the current currency does not guarantee for economy’s stability, and the value of gold was clearly proven during time of Prophet Muhammad and has been explained in Al-Qur'an and As-Sunnah.